Quasi-hydrostatic equation of state of silicon up to 1 megabar at ambient temperature - Anzellini, Simone; Wharmby, Michael T.; Miozzi, Francesca; Kleppe, Annette; Daisenberger, Dominik; Wilhelm, Heribert (Scientific reports, 2019)
The isothermal equation of state of silicon has been determined by synchrotron x-ray diffraction experiments up to 105.2 GPa at room temperature using diamond anvil cells. A He-pressure medium was used to minimize the effect of uniaxial stress on the sample volume and ruby, gold and tungsten pressure gauges were used. Seven different phases of silicon have been observed along the experimental conditions covered in the present study.